B.P.R.D. : vampire - Mignola, Mike; Moon, Fábio; Bá, Gabriel (B.P.R.D., 2013)
In the wake of the horrific events of B.P.R.D. 1948, we follow one doomed agent's quest for vengeance against the vampires of the world.